The fabrication of VOPcPhO nanoflowers and P3HT: VOPcPhO composite nanorods via template-assisted method / Anas Kamarundzaman - Kamarundzaman, Anas (2014)
In this study, the fabrication of vanadyl 2,9,16,23-tetraphenoxy-29H,31H phthalocyanine (VOPcPhO) nanoflowers and poly(3-hexylthiophene-2,5-diyl) (P3HT) : vanadyl 2,9,16,23-tetraphenoxy-29H,31H phthalocyanine (VOPcPhO) composite nanorods is reported. VOPcPhO nanoflowers and P3HT:VOPcPhO composite nanorods have been synthesised via the template-assisted method. VOPcPhO nanoflowers are prepared by varying the solution concentration (5 & 15mg/ml), spin coating rate (1000 & 2000 rpm) and annealing temperature (50 & 150 °C). P3HT:VOPcPhO composite nanorods have been synthesised from solution concentration of 5 mg/ml. Both VOPcPho nanoflowers and P3HT:VOPcPhO composite nanorods underwent a template’s dissolution. FESEM (Field Emission Scanning Electron Microscopy) and TEM (Transmission Electron Microscopy) images explained the growth mechanism of VOPcPhO nanoflowers and P3HT:VOPcPhO composite nanorods. Their morphological and structural properties are further characterized via FESEM and TEM. UV–vis spectra of VOPcPhO nanoflowers show a wider absorption at Q-band as compared to VOPcPhO thin films. P3HT:VOPcPhO composite nanorods show a same result as VOPcPhO nanoflowers. The wider band absorption and the shifted of peak absorption to the longer wavelength is observed in UV-vis spectrum which is caused by the improved interaction between small molecules and P3HT segment at their interfaces. The changes in Raman shift have also been observed which indicate the improvement of nanostructures exhibited by VOPcPhO and P3HT:VOPcPhO composite.